'The nightmare of multiculturalism': Interpreting and deploying anti-immigration rhetoric in social media. (March 2021) - Nortio, Emma; Niska, Miira; Renvik, Tuuli Anna; Jasinskaja-Lahti, Inga
Social media is an important transmitter of anti-immigration political rhetoric. In this study, we examine the discussions posted in a Finnish online forum provoked by an MP's anti-multiculturalist Facebook post. We draw upon frame analysis and discursive social psychology to analyse the communicative processes that challenge and normalise anti-immigration political rhetoric. Using frame analysis, we study how forum users entered heated societal discussion on multiculturalism by framing the MP's anti-multiculturalist address as either hate speech or – more dominantly – as normal political conduct. Using discursive social psychology, we examine constructions of multiculturalism in these discussions. We demonstrate how anti-immigration political communication was normalised, multiculturalism was constructed as a threat and the proponents of multiculturalism were discredited. We argue that to understand the rise of anti-immigration political movements, it is important to examine everyday political deliberation online as part of a wider discursive landscape.